2008
DOI: 10.1177/0022219408326221
|View full text |Cite
|
Sign up to set email alerts
|

Language-Minority Learners in Special Education

Abstract: Using data from the Early Childhood Longitudinal Study-Kindergarten Cohort, this study was designed to investigate proportional representation, identification rates, and predictors of language-minority (LM) learners in special education using a nationally representative sample of kindergarten, first graders, and third graders. The findings indicate that although LM learners were underrepresented in special education in kindergarten and first grade, they were overrepresented in third grade across all disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(100 citation statements)
references
References 20 publications
4
90
3
Order By: Relevance
“…Samson and Lesaux (2009) used the nationally representative dataset ECLS-K to determine that language minority students are identified later and in higher proportions than their native-English-speaking peers, being underrepresented in special education in kindergarten and first grade, but overrepresented by the 3 rd grade. This study suggests that the risk of identification with a learning disability may vary depending on when the student started attending school in the U.S., and official recognition as a language minority.…”
Section: Introductionmentioning
confidence: 99%
“…Samson and Lesaux (2009) used the nationally representative dataset ECLS-K to determine that language minority students are identified later and in higher proportions than their native-English-speaking peers, being underrepresented in special education in kindergarten and first grade, but overrepresented by the 3 rd grade. This study suggests that the risk of identification with a learning disability may vary depending on when the student started attending school in the U.S., and official recognition as a language minority.…”
Section: Introductionmentioning
confidence: 99%
“…This means that each professional has to decide what constitutes an impairment and where on the communication continuum differences are accepted as a freedom of expression outlined in the Universal Declaration of Human Rights (United Nations, 1948). This can put children from CLD backgrounds, whose communication patterns often do not fit the mainstream of public schools in the United States, at greater risk for identification as a special education student (Samson & Lesaux, 2009).…”
Section: Communication Judgmentmentioning
confidence: 99%
“…The researchers concluded that this was a result of insufficient knowledge of language acquisition. Samson and Lesaux (2009) agreed when they suggested that teacher ratings of language and literacy skills and reading proficiency were the significant predictors for referral to special education.…”
Section: Disproportionate Referral and Placement Of Ell Students In Smentioning
confidence: 93%
“…A number of researchers have suggested that there are a disproportionate number of ELL students referred to and placed in special education (Samson & Lesaux, 2009;Sullivan, 2011). Artiles, Rueda, Salazar, and Higareda (2005) examined the [1998][1999] school year data from 11 California urban school districts to determine if there was an over representation of ELL students referred to special education.…”
Section: Disproportionate Referral and Placement Of Ell Students In Smentioning
confidence: 99%
See 1 more Smart Citation